The Effect of Liquidity, Leverage, Sales Growth, and Cost-to-Revenue on the ROA of Indonesian Consumer Goods Companies - Bhimo Fadhel Musyaffa; Wahyu Ramadhan; Henny Setyo Lestari; Farah Margaretha Leon (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to analyze the effect of Liquidity Ratio, Leverage Ratio, Sales Growth, and Cost to Revenue Ratio on Return on Assets (ROA) in consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2024. The primary research problem focuses on how liquidity management, funding structure, sales growth, and cost efficiency determine profitability amidst intense competition and economic dynamics.Using an explanatory quantitative method, this research involves 53 companies selected through purposive sampling, resulting in a total of 318 observations. Secondary data were analyzed using panel data regression through software, with model selection procedures including the Hausman test and redundant fixed effects test.Theoretically, liquidity and sales growth are predicted to have a positive effect, while leverage and cost-to-revenue are expected to have a negative impact on ROA. This study also integrates control variables such as inventory turnover, Net Profit Margin (NPM), Average Collection Period (ACP), and firm size. In conclusion, operational efficiency and financial stability are crucial for management and investors in optimizing asset utilization to improve the financial performance of consumer goods companies in Indonesia.